2020
DOI: 10.1515/npprj-2019-0086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of a tactile sensor for measuring carton compliance

Abstract: This work reports the evaluation of a tactile sensor for the potential of using it to measure the compliance of folding cartons. A tactile sensor would make it possible to measure the mechanical behavior locally around the contact point, in contrast to existing methods that measure the global mechanical behavior of the carton. Research on the haptic sense has shown that the local mechanical behavior is more important than the global behavior when humans assess compliance of objects. It is shown that the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…In previous work we demonstrated that the biomimetic tactile sensor picks up differences in material properties [5]. We also explored the limits of repeatability for the measurement setup used here and formulated a procedure for conducting the measurements [6].…”
Section: Introductionmentioning
confidence: 99%
“…In previous work we demonstrated that the biomimetic tactile sensor picks up differences in material properties [5]. We also explored the limits of repeatability for the measurement setup used here and formulated a procedure for conducting the measurements [6].…”
Section: Introductionmentioning
confidence: 99%